If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Z + -4z = 9z + -9 + -1z Reorder the terms: Z + -4z = -9 + 9z + -1z Combine like terms: 9z + -1z = 8z Z + -4z = -9 + 8z Solving Z + -4z = -9 + 8z Solving for variable 'Z'. Move all terms containing Z to the left, all other terms to the right. Add '4z' to each side of the equation. Z + -4z + 4z = -9 + 8z + 4z Combine like terms: -4z + 4z = 0 Z + 0 = -9 + 8z + 4z Z = -9 + 8z + 4z Combine like terms: 8z + 4z = 12z Z = -9 + 12z Simplifying Z = -9 + 12z
| 2(5-2v)=5(v-5) | | 87-n=13 | | 24n^3+30n^2=0 | | -21a+28a-6=10 | | 4[(12+5)-1024]= | | 5y-15+6=5y+8-1x+17 | | 4x^2+6x+1=2x^2+6x-6+1 | | 8p+5-3=9+7p | | 3(d-2)=15 | | 3s+5w=19 | | 5x-54+3x+16=180 | | 2x^2=x^2-6 | | -4y=-x+6+zy | | 16x^4+32x^3+24x^2+8x-80=0 | | tan(x)=-0.364+0.57735027 | | 6-3u=21 | | n-6=13-4 | | 5-3(2x-4)=5(4x+2)-32 | | 80+.10x=132 | | 4x+48=828 | | (x^2-200x+4000log(x)-7200)=0 | | X+12y=23 | | -3a-7a=-3a-6a+7 | | 8u+2-4(-3u+2)=4(u-1) | | 9z+4-8=27 | | M+8=2m+1 | | -2(4s-5)-10=-2(6s+2)-2 | | 2x(x-3)=1+4x | | t^2-6t-4=0 | | F(-3)=9x-5 | | 12X^2-48X+34=0 | | 9y+2x(5y-19)=38 |